Pengaruh Propesionalisme Guru dalam Meningkatkan Kedisiplinan Belajar Siswa Di MA Yaqin Pemondah - Syahdan; Ozi Satria; Hilmizatul Milah (Pendidikan Al-Gafari, 2023)
Discipline is one element of the quality of human resources. Discipline can make someone feel obedient and obedient to the values they believe in so that they are more responsible for managing the order of personal and group life. Disciplining through education is the duty of every educational institution. Because with discipline all activities will run smoothly. This research is qualitative field research. Data collection techniques use interviews, observation, and documentation. The research aims to explain the role of class teachers in improving student learning discipline. The research results show that 1) There are programs organized by educational institutions, establishing school and class regulations, and involving students' parents. 2) In the learning process, discipline is essential, because that way students will feel comfortable and safe in the teaching and learning process and therefore teachers have their way or method of disciplining students in the learning process. 3) Driving and Inhibiting Factors are as follows: Its implementation has several supporting factors. The supporting factors include The same initiative, an association between student guardians, coordination from various parties, evaluation, provision of role models, and supporting facilities and infrastructure. Apart from supporting factors, there are also inhibiting factors. Factors inhibiting teachers' efforts to improve student discipline are different environments, parents who care less about their children, and the economy, and low IQ.